Representation of Islamic Children's Song Themes in Omar Hana - Sri Nurani; Fachri Helmanto (Mitra Palupi, 2021)
Background: Omar and Hana animated series songs can have different meanings; they can be represented. Such meanings are related to habluminallah, habluminannas, the relationship with knowledge, the relationship with animals, the relationship with plants and the relationship with the environment. Purpose: This study aims to determine the representation of the theme of Islamic children's songs in the animated series Omar and Hana. Design and methods: This research was carried out using a qualitative approach to content analysis methods with data collection techniques in the form of documents. The data was obtained from the video content and lyrics of the animated series Omar & Hana on the YouTube application of the Omar and Hana channel accounts for Islamic Kindergartens. Results: The results of this study reveal the representation of the theme of Omar and Hana's Islamic children's songs which are categorized into 6 parts, namely habluminallah consisting of (7 song titles), habluminannas (27 song titles), relationship with knowledge (1 song title) relationship with animals (2 titles). song), relationship with plants (1 song title) and relationship with environment (2 song titles).